Burnout Syndrome In The Peruvian Work Context: Critical And Detailed Literature Review - Condori Pineda , Daneza Isabel (2026)
The international scientific literature on the Burnout Syndrome (BS) construct is vast, however our objective is primarily based on knowing how this construct affects the Peruvian Work Context, from its main components and importance taking into account: Job satisfaction, organizational climate. , organizational commitment, quality of work life, engagement, coping strategies, resilience, personnel rotation and teleworking for the SB construct and Education, health, public administration, law enforcement, agricultural, commerce, financial communications, hotel, industrial, logistics, mining, retail, for the Peruvian work context. The main search engines are considered to be: La Reference, SciElo Magazine, Alycia, Dialnet and Google Academic. Keywords and a range of 5 years were determined as a limit for the analysis of publications or background information. This exercise resulted in a number of 300 matches of documents (articles, theses, among others), including research articles, scientific articles, case study. 40 ad hoc publications were selected. The results of the systematic review allowed us to conceptualize the effect of SB in the Peruvian work context, studied in 30 publications. After detailed analysis, we found that workers with moderate to high SB exhibit these characteristics: Chronic emotional exhaustion, cynicism and depersonalization, reduced personal accomplishment, physical problems, difficulty concentrating, changes in behavior and absenteeism from work. We conclude that: the prevalence levels of SB are increasing in the Peruvian workforce, it has a negative impact on organizational productivity, the well-being of workers and the economic growth of the country, on the other hand it emphasizes the importance of analyzing the differences in the incidence. of this syndrome among the different economic sectors and regions of Peru, which would allow more specific and contextualized interventions to be designed. It is necessary to investigate the impact of teleworking and the digitalization of work on the appearance and evolution of Burnout, analyzing hyperconnectivity, work flexibility and new forms of interaction and their impact both positively and negatively on workers. This study will be a contribution to new research in pursuit of finding a solution and improving the quality of the mental and physical health of workers in Peru.